Oil price swings - Mabro, R (Oxford Institute for Energy Studies, 2009)
The big oil price swing that occurred in 2007–9 has worried governments from oil-exporting and -importing countries. The main fact is well known. The price of WTI as it arises in the New York futures exchange (NYMEX) increased to an unprecedented height of more than $140 per barrel in early July 2008, and then collapsed in a free fall to a low of $32.40 per barrel in December 2008, less than six months later.